PEMBUATAN KERTAS DAUR ULANG DARI SAMPAH ORGANIK DAUN KERING DAN KERTAS BEKAS DI DESA KARANG INDAH - Athifah, Farhah; Ridlo, Azi Faiz; Iskandar, Tatang (Universitas Islam 45 Bekasi, 2024)
Karang Indah Village, located in Bojongmangu District, Bekasi Regency, faces challenges related to the underutilization of organic waste, particularly dry leaves and used paper. The accumulation and burning of dry banana leaves contribute to air pollution and environmental degradation. To address this issue, an eco-friendly recycled paper production initiative was developed by combining dry leaves and used paper to enhance the quality and durability of recycled paper. This initiative aims not only to support environmental sustainability but also to create economic opportunities for the local community through the development of recycled paper-based crafts. The program implemented various methods, including socialization, training, hands-on practice, and monitoring of the recycled paper production process. Participants were introduced to fundamental techniques in paper recycling, raw material processing, and product marketing strategies. The results demonstrated a significant increase in community awareness regarding sustainable waste management. Several participants successfully produced higher-quality recycled paper and began developing craft products such as greeting cards and book covers. Moreover, there was growing interest among the community members in establishing recycled paper-based businesses as an additional source of income. This program is expected to continue evolving as a model for effective and sustainable organic waste management, contributing to both environmental conservation and economic empowerment.